Exercise prescription for patients with multiple sclerosis; potential benefits and practical recommendations - Halabchi, Farzin; Alizadeh, Zahra; Sahraian, Mohammad Ali; Abolhasani, Maryam (BMC neurology, 2017)
Background Multiple sclerosis (MS) can result in significant mental and physical symptoms, specially muscle weakness, abnormal walking mechanics, balance problems, spasticity, fatigue, cognitive impairment and depression. Patients with MS frequently decrease physical activity due to the fear from worsening the symptoms and this can result in reconditioning. Physicians now believe that regular exercise training is a potential solution for limiting the reconditioning process and achieving an optimal level of patient activities, functions and many physical and mental symptoms without any concern about triggering the onset or exacerbation of disease symptoms or relapse. Main body Appropriate exercise can cause noteworthy and important improvements in different areas of cardio respiratory fitness (Aerobic fitness), muscle strength, flexibility, balance, fatigue, cognition, quality of life and respiratory function in MS patients. Aerobic exercise training with low to moderate intensity can result in the improvement of aerobic fitness and reduction of fatigue in MS patients affected by mild or moderate disability. MS patients can positively adapt to resistance training which may result in improved fatigue and ambulation. Flexibility exercises such as stretching the muscles may diminish spasticity and prevent future painful contractions. Balance exercises have beneficial effects on fall rates and better balance. Some general guidelines exist for exercise recommendation in the MS population. The individualized exercise program should be designed to address a patient’s chief complaint, improve strength, endurance, balance, coordination, fatigue and so on. An exercise staircase model has been proposed for exercise prescription and progression for a broad spectrum of MS patients. Conclusion Exercise should be considered as a safe and effective means of rehabilitation in MS patients. Existing evidence shows that a supervised and individualized exercise program may improve fitness, functional capacity and quality of life as well as modifiable impairments in MS patients.